Book review: McNicol, Sarah. Supporting people to live well with dementia: a guide for library services - Maceviciute, Elena (Information Research an international electronic journal, 2023)
McNicol, Sarah. Supporting people to live well with dementia: a guide for library services. London: Facet Publishing, 2023. xxviii, 182 p. ISBN 978-1-78330-597-1